PENGARUH PARTISIPASI ANGGARAN, KEJELASAN SASARAN ANGGARAN DAN KAPASITAS INDIVIDU TERHADAP KINERJA ANGGARAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PEMERINTAH DAERAH KOTA KUPANG) - Here, Kaleb Julio Rona; Henny A. Manafe; Rere Pauliana Bibiana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The objectives of this study were to: (1) Knowing the description of Budget Participation, Clarity of Budget Objectives and Individual Capacity on Budget Performance with Locus of Control as a Moderating variable in Local Government Kupang City, (2) Knowing the effect of Budget Participation variables, Clarity of Budget Objectives and Individual Capacity with Locus of Control moderating variables on Budget Performance as the dependent variable. The sample in this research was 117 State Civil Apparatus at the Kupang City Local Government. This type of research is quantitative research, the type of data used is secondary data, the data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The contribution of budget participation, budget target clarity and individual capacity to budget performance is 56.1% while the rest is influenced by other variables not included in this study. It is recommended that the Kupang City Local Government should maintain its optimistic personal character by holding trainings that can improve its abilities, so that budget performance can be better. To future researchers to be directed at a more in-depth study of other public sector organizations and the use of other variables need to be considered and have a wider scope.